Use of a novel through-the-needle biopsy forceps in endoscopic ultrasound - Shakhatreh, Mohammad H.; Naini, Sohrab Rahimi; Brijbassie, Alan A.; Grider, Douglas J.; Shen, Perry; Yeaton, Paul (Endoscopy International Open, 2016)
Background and aims: Pancreatic cysts are becoming more common. Their differential diagnosis includes benign, premalignant, and malignant lesions. Distinguishing the type of cyst helps in the management decision making. We report on a novel tissue acquisition device for pancreatic cysts.Methods: Data on two patients who underwent endoscopic ultrasound (EUS) – guided fine-needle aspiration with a new micro forceps device are presented.Results: Two patients had large pancreatic cystic lesions in the pancreatic head. Linear EUS was performed, and tissue samples were obtained with the Moray micro forceps through a 19-gauge needle. In both patients, mucinous columnar epithelium lined the cystic walls. One patient underwent surgical resection, and the other elected surveillance. Examination of the surgical specimen from the first patient confirmed the cyst was a side-branch intraductal papillary mucinous neoplasm (IPMN), gastric type.Conclusions: The Moray micro forceps is a new tool that can be used to help determine the nature of pancreatic cysts and aid in their risk stratification and management.